Benefitní odměňování zaměstnanců ve vybrané společnosti - Novosadová, Natálie (Vysoké učení technické v Brně. Fakulta podnikatelská, 2021)
Diplomová práce se zabývá návrhem na rozvoj systému odměňování zaměstnanců ve vybrané společnosti ABC s r.o. Práce je rozdělena na teoretickou, analytickou a návrhovou část. Teoretická část popisuje základní pojmy spadající do oblasti řízení a odměňování zaměstnanců. Analytická část se zaměřuje na analýzu vnitřního a vnějšího prostředí společnosti, na řízený rozhovor a dotazníkové šetření. V poslední části diplomové práce je představen návrh opatření ke zvýšení spokojenosti a loajality zaměstnanců.

The diploma thesis deals with a proposal for the development of a remuneration system in a selected company ABC s.r.o. The thesis is divided into theoretical, analytical and design part. The theoretical part describes the basic concepts in the field of management and remuneration of employees. The analytical part focuses on the analysis of the internal and external surroundings of the company, controlled interview and questionnaire survey. The last part of the diploma thesis deals with proposing measures to increase employee satisfaction and loyalty.
Benefit Remuneration of Employees in the Selected Company
Keywords: systém odměňování; odměňování; zaměstnanecké výhody; motivace; zaměstnanec; zaměstnavatel; remuneration system; remuneration; employee benefits; motivation; employee; employer